Prevalence and factors associated with musculoskeletal disorders and rheumatic diseases in indigenous Maya-Yucateco people: a cross-sectional community-based study. Issue 1 (July 2016) - Peláez-Ballestas, I.; Alvarez-Nemegyei, J.; Loyola-Sánchez, A.; Escudero, M.
Abstract This study aimed to estimate the prevalence of musculoskeletal disorders and rheumatic diseases in indigenous Maya-Yucateco communities using Community-Oriented Program for Control of Rheumatic Diseases (COPCORD) methodology. The study population comprised subjects aged ≥18 years from 11 communities in the municipality of Chankom, Yucatan. An analytical cross-sectional study was performed, and a census was used. Subjects positive for musculoskeletal (MSK) pain were examined by trained physicians. A total of 1523 community members were interviewed. The mean age was 45.2 years (standard deviation (SD) 17.9), and 917 (60.2 %) were women. Overall, 592 individuals (38.8 %; 95 % CI 36.3–41.3 %) had experienced MSK pain in the last 7 days. The pain intensity was reported as "strong" to "severe" in 43.4 %. The diagnoses were rheumatic regional pain syndromes in 165 (10.8 %; 95 % CI 9.4–12.5), low back pain in 153 (10.0 %; 95 % CI 8.5–11.6), osteoarthritis in 144 (9.4 %; 95 % CI 8.0–11.0), fibromyalgia in 35 (2.2 %; 95 % CI 1.6–3.1), rheumatoid arthritis in 17 (1.1 %; 95 % CI 0.6–1.7), undifferentiated arthritis in 8 (0.5 %; 95 % CI 0.2–0.8), and gout in 1 (0.06 %; 95 % CI 0.001–0.3). Older age, being female, disability, and physically demanding work were associated with a greater likelihood of having a rheumatic disease. In conclusion, MSK pain and rheumatic diseases were highly prevalent. The high impact of rheumatic diseases on daily activities in this indigenous population suggests the need to organize culturally-sensitive community interventions for the prevention of disabilities caused by MSK disorders and diseases.